Synthesis and properties of polylactide terpolymers P(LLA‐TMC‐GA) catalyzed by zirconium (IV) acetylacetonate. (5th December 2017) - Wen, Shaohua; Li, Yongfei; Chen, Weixing; Lei, Yaping; Luo, Chunyan; Hou, Yonggang
Abstract : A series of L‐lactide (LLA), 1, 3‐trimethylene carbonate (TMC) and glycolide (GA) terpolymers (LTG) of different monomer molar ratios were synthesized by using ring‐opening copolymerization. An effective and low‐toxic zirconium (IV) acetylacetonate Zr(Acac)4 was used as catalyst. The viscosity‐average molecular weights ( M η ) of obtained polymers were all above 2.2×10 4 g/mol. The chemical structure and viscosity of terpolymers were confirmed by Fourier transform infrared spectroscopy (FTIR), 1 H nuclear magnetic resonance ( 1 HNMR), 13 C nuclear magnetic resonance ( 13 CNMR) and an Ubbelohde viscometer. The thermal and mechanical properties were investigated by means of differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), X‐ray diffraction (XRD) and stress‐strain measurements. Results suggested that all terpolymers were amorphous and showed good thermal stability. Also it was found that elongation increased with the decreasing of LLA unit. More importantly, terpolymers displayed shape memory property when deformation temperatures were 14‐15 °C above T g . Abstract : A series of P(LLA‐TMC‐GA) were synthesized using a nontoxic and efficient Zirconium (IV) acetylacetonate as catalyst. All terpolymers were amorphous and random. More importantly, terpolymers displayed shape memory property above 14‐15 °C in Tg, which may find practical medical applications.